A Case for Rimantadine to Be Marketed in Canada for Prophylaxis of Influenza a Virus Infection - Fawziah Marra; Carlo A Marra; H Grant Stiver (Canadian Respiratory Journal)
PURPOSE: To evaluate the efficacy and safety of amantadine and rimantadine, the first generation antivirals, for the prophylaxis of influenza virus.